P026 Frequency of STD testing services among commercially-insured patients with high risk sexual behaviors. (14th July 2019) - Kumar, Sagar; Patel, Chirag; Tao, Guoyu
Abstract : Background: High-risk sexual behavior (HRSB) is associated with an increased burden of sexually transmitted diseases (STDs); therefore, CDC recommends those at high risk are screened more frequently than persons without HRSB. Because providers are able to document patients as having 3 types of HRSB: heterosexual, homosexual, or bisexual, using the International Classification of Disease Tenth Revision (ICD-10), this study assessed STD/HIV screening frequencies among patients with HRSB diagnoses. Methods: A large commercial claims database for outpatient visits for 2016 was analyzed. We included in the analysis patients diagnosed with any HRSB based on ICD-10 codes. The initial diagnosis for HRSB was considered as the index date for each patient. Testing frequencies for chlamydia, gonorrhea, syphilis, and HIV were assessed by 3 types of HRSB. For those diagnosed with HRSB from January 1-June 30, 2016, an additional 6 month follow-up testing period was also assessed. Results: 52, 160 patients were diagnosed with HRSB in 2016: 90.3% were heterosexual, 7.7% homosexual, and 2.1% bisexual HRSB. Testing for chlamydia, gonorrhea, syphilis, and HIV was 65.3%, 65.2%, 38.1%, and 43.6% for heterosexual, 49.9%, 49.8%, 51.5%, and 57.8% for homosexual, and 57.7%, 56.6%, 41.6%, and 48.2% for bisexual HRSB patients at the initial diagnosis date. 35.5%, 20.9%, and 36.5% of heterosexual, homosexual, and bisexual HRSB patients were found to have follow-up claims within 6 months after the index date, respectively. Of those who had follow-up claims, follow-up testing for chlamydia, gonorrhea, syphilis, and HIV was 77.2%, 77.6%, 50.6%, and 56.4% for heterosexual, 71.8%, 72.7%, 74.5%, and 80.4% for homosexual, and 69.7%, 71.1%, 58.2%, and 66.7% for bisexual HRSB patients. STD/HIV follow-up testing rates were higher among patients who were screened at the index date than those who were not. Conclusion: STD/HIV screening and follow-up screenings among HRSB patients are sub-optimal. Most HRSB patients do not have timely follow-up visits. Disclosure: No significant relationships.